Ideas Underlying a History of Invisibilized Feminine Nouns in the Public Opinion of the 18th and 19th Centuries - Sancha Vázquez, Julián (2022)
Linguistic studies on gender and words for men and women’s job titles have often been focused on the immediate temporal context. In contrast, this study has a historical sociolinguistic approach based on texts from the press of the eighteenth and nineteenth centuries, in order to find lexical innovations and speakers’ linguistic attitudes in regard to the grammatical gender system when referring to women in the professional field in the past. To this end, we will take into account the linguistic awareness of Spanish speakers, as well as their beliefs, ideas and ideologies about grammatical gender. We will try to show, through a series of testimonies, how the speakers of the past were already aware of their linguistic instrument when it served for the denomination of sexed beings and, above all, when and how they used it in relation to women.